A double-labeling procedure for sequence analysis of picomole amounts of nonradioactive RNA fragments. - Gupta, R C (1976)
A double-labeling procedure for sequence analysis of nonradioactive polyribonucleotides is detailed, which is based on controlled endonucleolytic degradation of 3'-terminally (3H)-labeled oligonucleotide-(3') dialcohols and 5"-terminal analysis of the partial (3H)-labeled fragments following their separation according to chain length by polyethyleneimine- (PEI-)cellulose TLC and detection by fluorography. Undesired nonradioactive partial digestion products are eliminated by periodate oxidation. The 5'-termini are assayed by enzymic incorporation of (32p)-label into the isolated fragments, enzymic release of (32p)-labeled nucleoside-(5') monophosphates, two-dimensional PEI-cellulose chromatography, and autoradiography. Using this procedure, as little as 0.1 - 0.3 A260 unit of tRNA is needed to sequence all fragments in complete ribonuclease T1 and A digests, whereas radioactive derivative methods previously described by us1-4 required 4 - 6 A260 units.